Stages Of Assessment Of Students’ Knowledge Using Intelligent Systems - Nuriev Alisher Qaraqulovich (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the specifics of using intelligent systems in the educational process, and discusses in detail the possibilities of automating assessment based on intelligent systems, which is one of the main types of educational process.